Thermal Performance and Natural Ventilation in Javanese Joglo Architecture: A Systematic Literature Review from an Ethnophysics Perspective - Qurrota A'yun; Rahmatta Thoriq Lintangesukmanjaya; Oktamia Ramadhani; Hidayatul Lathifah; Dwikoranto Dwikoranto; Lindsay Natalia Bergsma (Prodi S2 Pendidikan Fisika Universitas Negeri Surabaya, 2026)
Traditional Javanese Joglo architecture is widely recognized for its climatic adaptability; however, systematic understanding of its thermal performance and natural ventilation mechanisms, particularly from an ethnophysics perspective, remains limited and fragmented, with existing studies addressing cultural interpretations and building-physics performance separately. This study aims to synthesize existing research on the thermal and ventilation performance of Joglo and Joglo-type Javanese architecture and to interpret the findings through the lens of ethnophysics, linking cultural architectural practices with underlying physical principles. A systematic literature review was conducted following the PRISMA framework, resulting in six Scopus-indexed open-access studies published between 2017 and 2025. The reviewed studies employed computational simulations, field measurements, and qualitative analyses to examine indoor thermal conditions, airflow behavior, architectural geometry, and material characteristics. The synthesis reveals that thermal comfort in Joglo and Joglo-type architecture is primarily achieved through passive strategies. The reviewed evidence suggests that comfort is driven more by airflow and heat exchange processes than by substantial reductions in indoor air temperature. Wind-driven horizontal ventilation dominates in Joglo architecture, while comparative vernacular cases demonstrate complementary buoyancy-driven and material-mediated airflow mechanisms. These findings indicate that traditional architectural forms embody empirically grounded applications of heat transfer and fluid mechanics developed through cultural adaptation. Ethnophysics bridges traditional architecture, building physics, and physics education by linking Joglo design with heat transfer and airflow principles. This review helps readers understand indigenous architecture as applied physics, supporting physics education, sustainable design, and interdisciplinary research on vernacular adaptation.